A szovjet levelezőpajtás - Papp, Gábor Zsigmond (Hungary : Papp Gábor Zsigmond, 2011)
This story started thirty years ago. I was a seventh grader in the January of 1980 when I got a Soviet pen-friend. Our Russian teacher handed out some envelopes with Cyrillic writing on them saying that those were our pen-friends. I was lucky because mine was a girl from Moscow. Her name was Julia. We corresponded for three years and though we never met in person, I have kept all her letters. Now I decided to travel to Moscow, find her, and make a film about our childhood during the socialism.
Verzio Film Festival Submission
Duration: 00:54:00
Verzio Film Festival Submission